2014
DOI: 10.1155/2014/178298
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Reactions in Elderly Patients Hospitalized in a Multilevel Geriatric Hospital

Abstract: Background/Objectives. Blood transfusion is a critical issue for patients with chronic diseases such as heart failure, chronic kidney disease, and malignancy. However, side effects are not rare. The purpose of the study is to evaluate the frequency of adverse blood transfusion reactions in hospitalized elderly patients during a one-year period. Design/Setting/Participants. Blood transfusion reactions such as fever, chills, dyspnea, and others following blood transfusions in hospitalized geriatric patients duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…The median age in this study, carried out in a general hospital, was 70 years old, quite inferior to the findings of an American research which searched objective symptoms of transfusion reactions in the records of elders who received packed red blood cells, produced in a multi-level geriatric hospital, which found a median of 82 years (±9). However, the results of this research about the frequency of transfusions were corroborated by that study, which showed that 91% of patients received from one to two transfusions in the period (63%, one transfusion; and 28%, two transfusions) (36) .…”
Section: Discussionsupporting
confidence: 61%
“…The median age in this study, carried out in a general hospital, was 70 years old, quite inferior to the findings of an American research which searched objective symptoms of transfusion reactions in the records of elders who received packed red blood cells, produced in a multi-level geriatric hospital, which found a median of 82 years (±9). However, the results of this research about the frequency of transfusions were corroborated by that study, which showed that 91% of patients received from one to two transfusions in the period (63%, one transfusion; and 28%, two transfusions) (36) .…”
Section: Discussionsupporting
confidence: 61%
“…The find was consistent with studies conducted in Japan (5.05%), 12 India (3.4%), 24 Belgaum (4.41%), 25 and Nigeria (3.6%). 26 However, this finding was lower than a study conducted in different areas, namely, USA (16.5%) 27 and Nigeria (26.3%). 28 The observed difference might be due to a difference in study participants.…”
Section: Discussionmentioning
confidence: 57%
“…(Table 1) Lubart et al had high incidence of transfusion reactions in their study because their study population was hospitalized elderly individuals who are frail with a high rate of comorbidities. (8) The rate of transfusion reaction was higher (3.8%) in the study conducted by Pedrosa AKKV et al as their study included only paediatric population. The prevalence of transfusion reactions in children is high, and the intervening factors are: type of blood component, age, patient comorbidity, and multiple transfusions and type of blood component transfused.…”
Section: Discussionmentioning
confidence: 78%
“…Kumar P et al (6) 0.18% FNHTR Bhattacharya et al (7) 0.26% FNHTR Lubart et al (8) 10.5% FNHTR Pedrosa AKKV et al (9) 3.8% Allergic reactions…”
Section: Rate Of Trs Most Common Type Of Trmentioning
confidence: 99%